2014
DOI: 10.1681/asn.2013060675
|View full text |Cite
|
Sign up to set email alerts
|

Colony-Stimulating Factor-1 Signaling Suppresses Renal Crystal Formation

Abstract: We recently reported evidence suggesting that migrating macrophages (Mws) eliminate renal crystals in hyperoxaluric mice. Mws can be inflammatory (M1) or anti-inflammatory (M2), and colony-stimulating factor-1 (CSF-1) mediates polarization to the M2Mw phenotype. M2Mws promote renal tissue repair and regeneration, but it is not clear whether these cells are involved in suppressing renal crystal formation. We investigated the role of M2Mws in renal crystal formation during hyperoxaluria using CSF-1-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 61 publications
2
67
0
Order By: Relevance
“…Gene array profiling studies of the kidneys of CSF-1 deficient hyperoxluric mice showed disordered expression of anti- inflammatory genes and increase in CaOx crystal deposition indicating a critical role for CSF-1 signaling. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene array profiling studies of the kidneys of CSF-1 deficient hyperoxluric mice showed disordered expression of anti- inflammatory genes and increase in CaOx crystal deposition indicating a critical role for CSF-1 signaling. 27 …”
Section: Discussionmentioning
confidence: 99%
“…It was previously hypothesized, 9, 10, 27, 28 the kidney may actively remove interstitial crystal deposits through a cellular mechanism that includes a “sterile inflammation”. Our present and previous data suggest that enhanced production of certain cytokines/chemokines such as CCL2 by macrophages and epithelial cells in response to CaOx is an important part of such mechanism that involves several steps: a) recruitment of CCR2+ monocytes; b) in situ differentiation of recruited blood monocytes into “healing” anti-inflammatory macrophages and c) subsequent macrophage-mediated clearance of CaOx deposits.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we established the glyoxylate-induced crystal related kidney injury model following the method described previously (Okada et al, 2007, Taguchi et al, 2014. Then, we applied this model to investigate the protective effect and mechanism of OS using a metabonomics-based approach.…”
Section: Discussionmentioning
confidence: 99%
“…They are thought to contribute to the removal of crystal deposits via phagocytosis and digestion [1]. Consistently, colony-stimulating factor suppressed renal crystal deposition by inducing M2 macrophages in the kidneys of hyperoxaluric mice [43]. However, the molecular mechanisms that trigger the formation of crystal granulomas in crystalline CKD are unknown to date.…”
Section: Type 2 Crystalline Nephropathy: Intratubular Crystal Formationmentioning
confidence: 99%